Brain iron loading impairs DNA methylation and alters GABAergic function in mice. Issue 2 (2nd October 2018) - Ye, Qi; Trivedi, Malav; Zhang, Yiting; Böhlke, Mark; Alsulimani, Helal; Chang, JuOae; Maher, Timothy; Deth, Richard; Kim, Jonghan
ABSTRACT: Iron deficiency is closely associated with altered GABA metabolism and affective behavior. While mutation in the hemochromatosis ( HFE ) gene disrupts iron homeostasis and promotes oxidative stress that increases the risk of neurodegeneration, it is largely unknown whether HFE mutation modifies GABAergic homeostasis and emotional behavior. The goal of our study was to investigate the impact of HFE on GABAergic neurochemistry and redox–epigenetic regulation in the brain using H67D HFE‐mutant mice that recapitulates the H63D‐HFE mutation in humans. H67D mice displayed elevated redox‐active iron levels in the brain by 32% compared to age‐matched wild‐type mice. Moreover, the H67D brain had increased isoprostane and decreased glutathione, indicating elevated oxidative stress. Additionally, the H67D brain had decreased global methylation and attenuated DNA methyltransferase (DNMT) activity. Direct addition of iron to purified DNMT in vitro decreased enzyme activity in a concentration‐dependent manner. Last, H67D mice exhibited decreased anxiety‐like behavior, which was associated with increased expression of the GABAA receptor α2 subunits by 93%, and these changes were also observed in H67D mice fed a low‐iron diet. Taken together, our results suggest a putative role of HFE in regulating labile iron status in the brain, and mutation in H67D perturbs redox‐methylation status, contributing to GABAergic dysfunction.—Ye, Q., Trivedi, M., Zhang, Y., Böhlke, M., Alsulimani, H., Chang, J., Maher, T., Deth, R., Kim, J. Brain iron loading impairs DNA methylation and alters GABAergic function in mice. FASEB J. 33, 2460–2471 (2019). www.fasebj.org